2020
DOI: 10.2334/josnusd.20-0208
|View full text |Cite
|
Sign up to set email alerts
|

A new framework to identify dental emergencies in the COVID-19 era

Abstract: In order to reduce the spread of COVID-19 (Coronavirus Disease 2019), it is crucial to take extraordinary prevention and safety measures in dental offices, and to defer all elective and non-urgent procedures. Dental emergencies are defined through oral symptoms but, the systemic and psychological conditions of each patient should be considered. The present short communication proposes a multilevel evaluation (oral, systemic and psychological) and risk assessment score for the management of dental emergencies f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 7 publications
(10 reference statements)
0
6
0
1
Order By: Relevance
“…19,22 Although Alharbi et al concluded that there might not exist readily acceptable universal guidelines on preparing for the provision of dental care during the unfolding of any pandemic, 23 proposed standards for dental care have started to emerge related to COVID-19. 19,22,24,25 As these protocols are being made available, students pondered some of the items or factors that could be incorporated into them, from avoiding or minimizing the generation of aerosols, 22 to using a designated dental operatory for COVID-19-infected patients only. 26 Interestingly, no student mentioned the use of an assistant, even though a 4-handed technique is believed to be beneficial for controlling infection according to Meng et al 27 In terms of aerosols specifically, guidance might come from the 2003 SARS outbreak, where dental care was provided under strict personal protection equipment, with measures to reduce or eliminate the production of droplets and aerosols via high-volume aspiration, 28 and using negative pressure floor-to-ceiling closed operatories.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19,22 Although Alharbi et al concluded that there might not exist readily acceptable universal guidelines on preparing for the provision of dental care during the unfolding of any pandemic, 23 proposed standards for dental care have started to emerge related to COVID-19. 19,22,24,25 As these protocols are being made available, students pondered some of the items or factors that could be incorporated into them, from avoiding or minimizing the generation of aerosols, 22 to using a designated dental operatory for COVID-19-infected patients only. 26 Interestingly, no student mentioned the use of an assistant, even though a 4-handed technique is believed to be beneficial for controlling infection according to Meng et al 27 In terms of aerosols specifically, guidance might come from the 2003 SARS outbreak, where dental care was provided under strict personal protection equipment, with measures to reduce or eliminate the production of droplets and aerosols via high-volume aspiration, 28 and using negative pressure floor-to-ceiling closed operatories.…”
Section: Discussionmentioning
confidence: 99%
“…Although Alharbi et al. concluded that there might not exist readily acceptable universal guidelines on preparing for the provision of dental care during the unfolding of any pandemic, 23 proposed standards for dental care have started to emerge related to COVID‐19 19,22,24,25 . As these protocols are being made available, students pondered some of the items or factors that could be incorporated into them, from avoiding or minimizing the generation of aerosols, 22 to using a designated dental operatory for COVID‐19‐infected patients only 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have recommended a scoring framework for identifying dental emergencies during the current pandemic. 19 This is based on the severity of the oral condition, systemic health and anxiety. Although this has not been validated in any patient group, the mandatory completion of such a scoring system on digital referrals may aid decision making.…”
Section: Discussionmentioning
confidence: 99%
“…Como resultado da busca e leitura dos artigos na íntegra, foram encontrados estudos que traziam somente um dos termos para referenciar todas as situações de urgência ou de emergência odontológica. Alguns desses estudos fizeram uso apenas do termo "emergência odontológica" 32,33,27,15,35,36,18,19,61,37,21,42,43,44,55,57,47,24,31,56,50,59 , enquanto outros, em menor número, traziam o termo "urgência odontológica" na referência de toda e qualquer situação 54,48,52…”
Section: Materiais E Métodosunclassified